Benefit-risk profile of longer-than-1-year dual antiplatelet therapy in TWLIGHT-like patients with high risk of ischemic or bleeding events after drug-eluting stents implantation. (25th November 2020) - Wang, H.Y; Gao, R; Xu, B.O; Dou, K; Kirtane, A
Abstract: Background: Dual-antiplatelet therapy (DAPT) exceeding 1 year may increase a bleeding risk despite reducing the risk of ischemic events. The benefits and harms of prolonging DAPT with aspirin and clopidogrel beyond 1 year after percutaneous coronary intervention (PCI) with drug-eluting stent (DES) implantation for TWLIGHT-like patients with high-risk for bleeding or an ischemic event remain unknown. Method: Between January 2013 and December 2013, all consecutive patients undergoing PCI were prospectively included in the Fuwai PCI Registry. We evaluated 7521 patients who were at high risk for ischemic or hemorrhagic complications and were events free (no death, myocardial infarction [MI], stroke, stent thrombosis [ST], any revascularization, or major bleeding) at 1 year after the index procedure. Subjects were divided into 2 groups: DAPT >1-year group (n=5252) and DAPT ≤1-year group (n=2269). Patients at high-risk for ischemic or bleeding events were defined as having at least one additional clinical feature and one angiographic feature according to TWILIGHT trial criteria. The clinical criteria for high risk were age ≥65 years, female sex, troponin-positive ACS, established vascular disease, diabetes mellitus that was being treated with medication, and CKD. Angiographic criteria included multivessel coronary artery disease, total stent length ≥30 mm, a thrombotic target lesion, a bifurcation lesion treated with two stents, an obstructive left main or proximal left anterior descending lesion, and a calcified target lesion treated with atherectomy. The primary outcome was major adverse cardiac and cerebrovascular events [MACCE] (a composite of all-cause death, MI, or stroke). Results: During a median follow-up of 30 months after the index procedure, DAPT >1-year was associated with a reduction in risk for MACCE compared with DAPT ≤1-year (1.5% vs. 3.8%; adjusted hazard ratio [HR]: 0.36; 95% confidence interval [CI]: 0.27–0.50; P<0.001) after multivariable adjustment. This difference was largely driven by a lower risk of all-cause mortality. In contrast, the risk of BARC type 2, 3 or 5 bleeding was statistically similar between the 2 groups (1.0% vs. 1.1%; adjusted HR: 0.81; 95% CI: 0.50–1.30; P=0.373). After propensity score matching, incidence of MACCE was still lower in the DAPT >1-year group than the DAPT ≤1-year group (1.6% versus 4.5%; HR, 0.34; 95% CI, 0.22–0.52; P<0.001) and the rates of BARC type 2, 3 or 5 bleeding was not different between the 2 groups (1.1% versus 0.9%; adjusted HR, 1.12; 95% CI, 0.57–2.18; P=0.744). In subgroup analysis, the treatment effect of prolonged DAPT was consistent across subgroups regardless of ACS, DAPT score, or type of used DES. Conclusions: DAPT continuation with aspirin and clopidogrel beyond 1-year after DES implantation resulted in a significantly lower rate of MACCE, with no higher risk of clinically relevant bleeding in TWLIGHT-like patients who were at high-risk for ischemic or bleeding events. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): National Natural Science Foundation of China